Food insecurity and nutritional status of individuals in a socially vulnerable situation in Brazil/Inseguranca alimentar e estado nutricional entre individuos em situacao de vulnerabilidade social no Brasil - Godoy, Katia; Savio, Karin Eleonora de Oliveira; Akutsu, Rita de Cassia; Gubert, Muriel Bauermann; Botelho, Raquel Braz Assuncao (Ciência & saude coletiva, 2017)
The objective was to investigate the association between food insecurity (FI) and anthropometric indicators among beneficiaries of a Brazilian social program called Community Canteens (CCs). This was a cross-sectional study. The associations were analyzed by chi-square test and Poisson regression. The subjects were 1,232 patrons of Brazil's CCs. Men with severe FI had a lower mean BMI (-1.53 kg/m2) and a lower body fat percentage (-3.83 percentage points). Men that had a fat percentage classified as "risk of diseases associated with malnutrition" had a 2.34 times greater chance of experiencing severe FI, as did those who had low weight (PR: 2.64). However, these results were no longer significant after Poisson regression. With respect to women, there were no significant associations between the variables studied and FI. The high prevalence of overweight and body fat in the population at all of the FI levels and for both sexes are an indication of the complexity of the Brazilian scenario regarding the aspect of nutrition and excess weight in poor communities.